2000
DOI: 10.2166/wst.2000.0469
|View full text |Cite
|
Sign up to set email alerts
|

Experimental comparison between MBBR and activated sludge system for the treatment of municipal wastewater

Abstract: The aim of the described experimentation was the comparison of a low cost MBBR and an activated sludge system (AS). The MBBR applied system consists of the FLOCOR-RMP® plastic media with a specific surface area of about 160 m2/m3 (internal surface only). The comparison with activated sludge (AS) was performed by two parallel treatment lines. Organic substance removal and nitrification were investigated over a 1-year period. Comparing the results obtained with the two lines, it can be observed AS totCOD removal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(55 citation statements)
references
References 8 publications
4
48
0
3
Order By: Relevance
“…MBBR technology offers a number of advantages over conventional technologies for treating waste, including a high effluent quality, no bulking problems, and lower cost. Other advantages of fixed biofilm growth include the decoupling of biomass retention from hydraulic retention time leading to longer sludge ages and low waste sludge volumes (5,37).…”
mentioning
confidence: 99%
“…MBBR technology offers a number of advantages over conventional technologies for treating waste, including a high effluent quality, no bulking problems, and lower cost. Other advantages of fixed biofilm growth include the decoupling of biomass retention from hydraulic retention time leading to longer sludge ages and low waste sludge volumes (5,37).…”
mentioning
confidence: 99%
“…Statistical analysis confirmed the statistically significant differences between results for the MBBR and Mammoth reactors, with exception of changes in theconcentration of NO 2 -ions. Many authors have confirmed the effectiveness of the reduction of organic pollutants in MBBR reactors [14,17,18]there are no articles devoted to acomparison of the type of aeration in the wastewater treatment efficiency for MBBR reactors, which differ in the types of aerators. The nutrients level analyses also showed statistically significant differences in changesof their concentrations PO 4 3-(11 -80%) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…So, excellent NH 4 -N conversion was obtained at overall loads up to 0.3132 g NH 4 -N m −2 day ). Andreottola et al, [16] observed an average nitrification rate as 1.84 g NO 3 -N kg VSS −1 h −1 [17] . Three factors, the load of organic matter, the ammonium concentration and the oxygen Organic load controls nitrification and should be as low as possible.…”
Section: −1mentioning
confidence: 98%
“…There are presently more than 400 large-scale wastewater treatment plants based on this process in operation in 22 different countries all over the world [8] . During the past decade it has been successfully used for the treatment of many industrial effluents including pulp and paper industry waste [9] , poultry processing wastewater [10] , cheese factory wastes [11] , refinery and slaughter house waste [12] , phenolic wastewater [13] , dairy wastewater [14] and municipal wastewater [15][16][17][18][19][20][21][22] . Moreover, sequencing batch operation of MBBR has been attempted for biological phosphorus removal [4,23] , whereas documents and practical experiences with biological nitrogen and phosphorus removal in MBBR process with continuously operation aren't available in Iran and other countries.…”
Section: Introductionmentioning
confidence: 99%